Towards a Process for NFRs Evaluation in IoT Applications - Paiva, Joseane O. V.; Carvalho, Rainara M.; Andrade, Rossana M. C. (Anais do Simpósio Brasileiro de Computação Ubíqua e Pervasiva (SBCUP); 2022: Anais do XIV Simpósio Brasileiro de Computação Ubíqua e Pervasiva, 2022)
The Internet of Things (IoT) is a paradigm characterized by a variety of objects that interact with each other using the internet to achieve common goals. IoT applications are more and more present in our lives, either in our homes, or on the streets, or in our work environments. These applications bring new Non-Functional Requirements highly related to the user interaction quality, such as context-awareness, synchronicity, and calmness. The evaluation of these NFRs can be challenging, because we may have to take into account qualitative and quantitative aspects. In this way, the evaluators can be confused about the steps they need to follow and the best order to perform the NFRs evaluation. After conducting a systematic mapping study about the NFR evaluation in IoT applications, we could not find a process that systematizes these activities stepby-step. Therefore, this paper proposes a process for evaluating non-functional requirements in IoT applications. This process divides the quality evaluation into two aspects, qualitative and quantitative, to capture quality measurements and subjective aspects of the IoT applications. To verify whether the established process meets the evaluators' needs, we applied 2 questionnaires with the experts and, based on the obtained results, we made some adjustments and came up with a preliminary version of the process that is presented in this paper.